Developing an Evidence-Based Fall Prevention Curriculum for Community Health Workers - St. John, Julie A.; Shubert, Tiffany E.; Smith, Matthew Lee; Rosemond, Cherie A.; Howell, Doris A.; Beaudoin, Christopher E.; Ory, Marcia G. (Frontiers in Public Health, 2015)
*